(untitled) (Ius Novum, 2023)
This article explores the involvement of members from both Polish and foreign consular posts in the process of taking evidence in criminal proceedings. Specifically, it examines the participation of Polish consular officers in the interrogation of witnesses and defendants, as outlined in Article 177 § 1b(2) of the Polish Code of Criminal Procedure. Additionally, the article discusses interrogation of these parties by consuls acting on behalf of Polish courts. Governed by both Polish and international law, this process is situated within the realm of international criminal proceedings and consular law. The article also delves into the right to decline to give evidence, a privilege granted to members of consular posts based on their official functions. In this context, we introduce the concept of ‘consular secrecy’, which can be likened to professional secrecy or secrecy associated with the official roles of certain individuals.